MENERAPKAN KONSEP PENGAMBILAN KEPUTUSAN TAKTIS DALAM BERBAGAI SITUASI BISNIS PADA APLIKASI SHOPEE KOTA KENDARI - Unci, Ana Yuri (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
Abstract: The purpose of the research is to apply the concept of tactical decision making in various business situations related to the Shopee application in Kendari City. This research uses a case study method by collecting data through interviews, observations, and study of related documents. The results show that the use of appropriate analytical techniques, such as SWOT analysis, Porter's Five Forces analysis, and cost-benefit analysis, business managers can make more effective decisions. Through market understanding and user segmentation, business managers can develop appropriate marketing strategies to reach the target market more effectively. Applying the Concept of Tactical Decision Making in Various Business Situations on the Shopee Application in Kendari City. In an increasingly advanced digital era, technology-based applications have become an important tool in running a business. One of them is the Shopee application, an e-commerce platform that makes it easy for users to shop online.